Pengaruh Brand Image Terhadap Keputusan Tamu Menginap Di Four Points By Sheraton Batam - Fitri Chairani; Nidia Wulansari (Pusat Riset dan Inovasi Nasional, 2023)
The research was motivated by post-stay guest complaints regarding the decision to stay and one of the factors, namely brand image hotel. This research was conducted with the aim of exploring how far brand image can influence the decisions of guests who choose to stay at Four Points by Sheraton Batam. This research is quantitative and uses a causal associative method. The population that is the focus of the research is guests who have had the experience of staying at the Four Points by Sheraton brand. In this research, samples were taken from 98 respondents using the purposive sampling method. Our research instrument is a questionnaire designed with a Likert scale. The data obtained will be analyzed using SPSS version 26.00 software, and the results of the analysis will be presented in tabular form. Research results included brand image (X) at Four Points by Sheraton Batam in the good category with a percentage of 35.7%. Guest Decision to Stay (Y) at Four Points by Sheraton Batam in the good category 43.9%. Simple regression test with T test on variables brand image influences the guest's decision variables to stay at Four Points by Sheraton Batam. Variable F value brand image (X) has a simultaneous impact on the guest's decision to stay (Y) at Four Points by Sheraton Batam. Adj Value R square 0.796 means variabel brand Image 79.6% influence on guests' decision to stay at Four Points by Sheraton Batam and 20.4% impact from different variables.